(untitled) (Medico Legal Update, 2021)
The purpose of this study is to assess anxiety and stress in college student before and after midterm exam. The study will be conducted on N=200 students of Galgotias University, Greater Noida, U.P., India. Scale is taken as outcome measure and students are asked to fill a form (according to DASS and PSS) after taking consent before and after midterm examination. There collected data is then to be compared to know the effect of exams on stress and anxiety level of students. Background: The spiritual well-being of university student is an area of amplify reflection universal. The aim of this student is to check-up the expansion of stress and concern into a group of Galgotias university student. Solely as each young person, undergraduate students needfulness to cope. Method: We are taking 200 subjects for this study. My study is based on observational study. We are using DASS and PSS scale for measuring the stress and anxiety of the students. Inclusion criteria is stress and anxiety in college student during midterm exam and exclusion criteria is neurological and psychological disorders. Results: We are hoping for positive result. We would find that the students take exam stress and anxiety level increase. Discussion AND Conclusion: We would conclude positive result of our study. Our study will show that during and before exam students face stress and anxiety and after exam it will decrease.